Intrapersonal and Interpersonal Concomitants of Facial Blushing during Everyday Social Encounters - aan het Rot, Marije (PLoS One, 2015)
Facial blushing may usually be undesirable but may have an ameliorative function for some individuals under some circumstances. Researchers have studied the blush in laboratory settings, but not in daily life. In the present research, conducted with young adults, we employed for the first time an event-contingent recording method for assessing facial blushing during every-day social encounters. Blushing was associated with feeling embarrassed, ashamed, and exposed. These findings, though based on correlational analyses, are consistent with the idea that blushing is often unpleasant and can be maladaptive, and may contribute to the common belief that blushing is an undesirable response. Frequent blushers generally reported lower levels of dominant behavior, higher levels of submissive behavior, and perceived their social interaction partners as more powerful and less affiliative. This was independent of whether they blushed or not, suggesting that altered social behaviors and perceptions are associated with blushing-associated traits rather than with the blushing state. The experience of the blush varied as a function of the frequency with which a person blushed. Blushing was associated with higher levels of shame in frequent blushers than in infrequent blushers. In infrequent blushers, blushing was associated with higher levels of pleasant affect, suggesting that for infrequent blushers the blush may occur in positive social encounters.